Teacher's Strategy in Developing Practical Values of the 5th Pancasila Precepts in Thematic Learning in Elementary School - Febri Tia Aldila; Endah Febri Setiya Rini (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to find out and describe the strategies that teachers can use to develop the practical value of the five Pancasila precepts in the thematic learning process for first grade students at elementary school 36/I Kilangan. Methodology: This research is a qualitative research with a phenomenological approach. The samples in this study were school principals, teachers, and 2 low grade students at elementary school 36/I Kilangan. Collecting data in this study using observation sheets, interview guide instruments. in this study using the Miles and Huberman analysis technique. Main Findings: The teacher's strategy in instilling the practical values of Pancasila, especially the precepts